Asupan Zat Gizi Makro Penderita DM Tipe II yang Mengkonsumsi dan Tidak Mengkonsumsi Makanan Komersial Nihil Perbedaan - Sri Purnama; Anang Wahyudi; Jumiyati Jumiyati (Poltekkes Kemenkes Jakarta III, 2018)
Diabetes mellitus is a metabolic disease group with hiperglikemi characteristics that occur due to abnormalities of insulin secretion, insulin work or both.Food play an important role in providing nutrition for diabetics.Intake of foods containing carbs, protein and fat is an important nutrient, extra food for diabetics in the form of low-calorie sugar, milk, biscuits, yogurt, whole wheat bread, oats are sold commercially. Objectives: To know the difference in intake of Nutrients Macro Against Diabetes mellitus type II Sufferers consume such foods because commercial foods providing nutrients according to needs, and deliver practical benefits. Method: This is an observational cross sectional design research. It was carried out in April-May 2018. Samples gathered at the RSUD Dr. M Yunus Bengkulu and selected by purposive sampling in accordance to inclusion and exclusion criteria. Total sample were 33 respondents. This research used the FFQ for intake data.The data were tested using the Kolmogorov-Smirnov test, independent t-test. Results: The majority of respondents were women. Respondents who choose to consume commercial foods were 63.6%, the rest (36.4%) chose not to consume commercial food. The results of this research obtained no difference between macro-nutrients intake in diabetes mellitus type II patient that consumes commercial and non commercial food (p value: 0.32), energy intake (p value: 0.67), protein intake (p value: 0.94) and fat intake (p value: 0.11) carbohydrates intake. Conclusion : Diabetics mellitus patients can consume commercial foods recommended for diabetes mellitus diet.